Neoadjuvant Chemotherapy Is Associated With Prolonged Primary Treatment Intervals in Patients With Advanced Epithelial Ovarian Cancer. Issue 1 (1st January 2011) - Milam, Michael R.; Tao, Xia; Coleman, Robert L.; Harrell, Robyn; Bassett, Roland; dos Reis, Ricardo; Ramirez, Pedro T.
Abstract : Background: We evaluated the impact of neoadjuvant chemotherapy (NC) relative to primary surgery (PS) to determine if there was a difference in the total time and number of chemotherapy cycles given in patients with advanced epithelial ovarian cancer. Methods: We identified 263 consecutive women meeting eligibility from 1993 to 2005 for this institutional review board-approved study. Eligible patients in this analysis were those women with advanced disease (stage IIIC-IV) in whom a maximal cytoreductive effort was planned either at PS or after NC. Time to start chemotherapy was defined as follows: (1) NC group: confirmation of diagnosis through biopsy, cytological diagnosis from ascites, and pleural effusion; (2) PS group: confirmation of diagnosis from the date of surgery that confirmed the diagnosis of epithelial ovarian cancer. Total chemotherapy cycles: (1) NC group: NC chemotherapy cycles plus postoperative cycles; (2) PS group: chemotherapy after primary tumor debulking surgery. Clinical information evaluated included chemotherapy type, chemotherapy cycle number, total time to administer frontline chemotherapy, and survival. Results: Median chemotherapy cycles were greater in the NC group compared with the PS group (9 [range, 4-30] vs 6 [range, 3-19]; P < 0.01). The PS group was also more likely to undergo chemotherapy regimens involving platinum and taxane treatment compared with the NC group (79% vs 65%; P = 0.017). Total time undergoing primary chemotherapy from initial diagnosis was greater in the NC group compared with PS (223 vs 151 days; P < 0.01). No significant difference was observed in overall survival and progression-free survival in the 2 groups. Conclusions: In patients with advanced ovarian cancer, NC followed by abdominal hysterectomy is associated with improved perioperative outcomes including optimal cytoreduction, decreased blood loss, and decreased inpatient hospitalization. In this cohort, NC was also associated with prolonged chemotherapy treatment intervals and increased chemotherapy cycles without improvement in survival.